Structural studies of MUC1 core related peptides - Scanlon, Martin J. (1993)
Polymorphic epithelial mucins are large complex glycoproteins which consist of a single polypeptide backbone, a large domain of which is usually made up of degenerate tandem repeats. One such molecule MUC1 is expressed at the surface of human mammary cells and is developmentally regulated and aberrantly expressed in tumours. These mucins have been identified as the target antigens for a number of murine monoclonal antibodies raised against a variety of immunogens including human milk products and breast tumour extracts. The anti-MUC1 antibodies have been shown to display tumour reactivity and have been used both as agents for imaging and in immunoassays to assess tumour burden and response to therapy. A number of these antibodies have been found to define epitopes within the tandem repeat of the protein core of the MUC1. Hydropathicity calculations and secondary structure predictions on the twenty amino acid tandem repeat of the MUC1 core protein have identified a hydrophilic domain Pro-Asp-Thr-Arg-Pro-Ala-Pro, which has a high probability of turn formation. It is within this domain that the epitopes of the anti-MUC1 antibodies are found. High field N.M.R. studies undertaken on an antigenic twenty amino acid peptide corresponding to the tandem repeat sequence of MUC1 in dimethyl sulphoxide have identified the presence of a type-I beta-turn in the region Pro-Asp-Thr-Arg. This turn overlaps the epitopes of all of the MUC1 antibodies characterised to date. In an attempt to identify more precisely the conformational requirements for binding to two anti-MUC1 antibodies, HMFG1 and HMFG2, the solution structures of several MUC1 core related peptides in dimethyl sulphoxide have been investigated. All of the peptides studied have been found to contain either beta-turns or modified turns which overlap their hydrophilic epitope domains. While these observations may provide some explanation for the observed reactivity of the different peptides, they give little insight into the precise structural requirements for antibody binding. Due to the flexibility of linear peptides in solution it is not possible to define the side chain conformations which are crucial to the processes of antibody recognition. In order to define the bound conformations of antigenic peptides using N.M.R. it is necessary to undertake experiments in the presence of antibody. Initial experiments have been performed in order to determine the conformation of the MUC 1 core related twenty amino acid peptide when bound to the anti-mucin antibody C595. In addition DNA coding for the variable domains of C595 has been cloned and sequenced in order to facilitate both expression of recombinant antibody binding fragments and the modelling of the binding site. These studies should provide a clearer understanding of the structural basis of antibody recognition of the peptides, and may give an insight into the specificity of anti-MUC1 antibodies for malignant cells.